Isotopic disproportionation during hydrogen isotopic analysis of nitrogen‐bearing organic compounds. (26th March 2015) - Nair, Sreejesh; Geilmann, Heike; Coplen, Tyler B.; Qi, Haiping; Gehre, Matthias; Schimmelmann, Arndt; Brand, Willi A.
Abstract : Rationale: High‐precision hydrogen isotope ratio analysis of nitrogen‐bearing organic materials using high‐temperature conversion (HTC) techniques has proven troublesome in the past. Formation of reaction products other than molecular hydrogen (H2 ) has been suspected as a possible cause of incomplete H2 yield and hydrogen isotopic fractionation. Methods: The classical HTC reactor setup and a modified version including elemental chromium, both operated at temperatures in excess of 1400 °C, have been compared using a selection of nitrogen‐bearing organic compounds, including caffeine. A focus of the experiments was to avoid or suppress hydrogen cyanide (HCN) formation and to reach quantitative H2 yields. The technique also was optimized to provide acceptable sample throughput. Results: The classical HTC reaction of a number of selected compounds exhibited H2 yields from 60 to 90 %. Yields close to 100 % were measured for the experiments with the chromium‐enhanced reactor. The δ 2 H values also were substantially different between the two types of experiments. For the majority of the compounds studied, a highly significant relationship was observed between the amount of missing H2 and the number of nitrogen atoms in the molecules, suggesting the pyrolytic formation of HCN as a byproduct. A similar linear relationship was found between the amount of missing H2 and the observed hydrogen isotopic result, reflecting isotopic fractionation. Conclusions: The classical HTC technique to produce H2 from organic materials using high temperatures in the presence of glassy carbon is not suitable for nitrogen‐bearing compounds. Adding chromium to the reaction zone improves the yield to 100 % in most cases. The initial formation of HCN is accompanied by a strong hydrogen isotope effect, with the observed hydrogen isotope results on H2 being substantially shifted to more negative δ 2 H values. The reaction can be understood as an initial disproportionation leading to H2 and HCN with the HCN‐hydrogen systematically enriched in 2 H by more than 50 ‰. In the reaction of HCN with chromium, H2 and chromium‐containing solid residues are formed quantitatively. Copyright © 2015 John Wiley & Sons, Ltd.